PENDIDIKAN DI INDONESIA (1945-1950) - ALINUR . (LP2MTBM MAKARIOZ, 2020)
Because of the time of Japanese occupation, the students were forced to join the military training, so at the time of armed struggle they were able to adapt and went into the war in the first line. The organization of IPI (Indonesia Students Union) was held as one part og the defence. Besides, there were many organization or armed strugglers which all of the members were students. When BKR (The Safety of Society Corp), TKR (The Safety of Society Army) were formed then it changed became TRI (The Republic of Indonesia Army), so there were so many students joined with it. They were under the command of TRI like CPS (Siliwangi Students Corps) in West Java, TRIP (The Trio Students) and Ronggolawe Students Troops in East Java, IMAM Troops (Indonesia is free or die) in Middle of Java. The example of The Students Union which was standing alone were Kere Lines, Ksatria Lines, Jemble Lines, Jelata Lines and Students of BPRI in the Middle of Java region.